PENGGUNAAN RHIZOBIUM DAN MIKORIZA UNTUK PERTUMBUHAN Calliandra calothyrsus UNGGUL - Rina Laksmi Hendrati; Siti Husna Nurrohmah (Jurnal Pemuliaan Tanaman Hutan, 2016)
Calliandra calothyrsus, a rhizobium associated legume, fixes atmospheric nitrogen by forming root nodules. Rhizobium availability is crucial for Calliandra’s growth especially on new sites. Additive or synergic effects of rhizobium and mycorrhiza are found to improve seedling quality. Genetically improved Calliandras require optimum silvicultural practices including rhizobium and mycorrhiza application and differences among families need to be observed. This followed with combination treatment of 5g rhizobium and different mycorrhiza level at 0, 5 and 10g applied to 5 families in 30 x 30 cm polybag. Assessments were for leaf number, height, diameter at 1, 4 and 8 weeks and number of root nodules at 4 and 8 weeks after application. Results show that rhizobium application has no significant effects although it enhances grow, while mycorrhiza application improve leaf number after 14 weeks. Second experiment for 3.5 month seedlings, indicates interaction on family-mycorrhiza level to seedling height and root nodules. Very positive correlations show that more root nodules improved leaf number (r=0.41), height (r=0.3) and diameter (r=0.45) up to planting time. Quite cheap rhizobium and mycorrhiza application is therefore beneficial to optimize the growth of genetically improved C. calothyrsus, although genotype differences may eXist.